Rancangan Sistem Penjualan dan Stok Opname Berbasis Web pada CV Marga Mulja Abadi - Tony Setiawan; Farizi Ilham; Derio Dimas Riyadi; Riki Reza Ryansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This study aims to design a sales and stock opname information system for CV MARGA MULJA ABADI to improve the efficiency of sales data management and inventory control. The problem currently faced by the company is that the sales recording and stock checking processes are still done manually, which can potentially lead to recording errors, delayed information, and difficulties in monitoring product availability. The methods used in this research include data collection through observation, interviews with employees, warehouse heads, and the owner, as well as literature studies. The system development employs the SDLC Waterfall method with stages of analysis, design, implementation using the Laravel framework and MySQL database, and testing. The output of this research is a web-based sales and stock opname system design capable of managing product data, sales transactions, supplier management, periodic stock opname features, minimum stock notifications, sales receipt printing, as well as real-time sales reports and stock cards. This system is expected to improve stock data accuracy, accelerate the report recapitulation process, and facilitate asset monitoring and decision-making related to inventory.